2021-03-22 23:25:22 +00:00
\documentclass [../../script.tex] { subfiles}
% !TEX root = ../../script.tex
\begin { document}
\section { Convergence of Series}
\begin { defi}
Let $ \rcseqdef { x } $ . Then the series
\[
\series { k} x_ k
\]
is the sequence of partial sums $ \seq { s } $ :
\[
s_ n = \series [n] { k} x_ k
\]
If the series converges, then $ \series { k } $ denotes the limit.
\end { defi}
\begin { thm} \label { thm:seriesnull}
Let $ \rcseqdef { x } $ . Then
\[
\series { n} x_ n \text { converges} \implies \seq { x} \text { null sequence}
\]
\end { thm}
\begin { proof}
Let $ s _ n = \series { n } x _ n $ . This is a Cauchy series. Let $ \epsilon > 0 $ . Then
\begin { equation}
\exists N \in \natn ~\forall n \ge N: ~~|s_ { n+1} - s_ n| = |x_ { n+1} | < \epsilon
\end { equation}
\end { proof}
\begin { eg} [Geometric series]
Let $ x \in \realn $ (or $ \cmpln $ ). Then
\[
\series { k} x^ k
\]
converges if $ |x| < 1 $ . (Why?)
\end { eg}
\begin { eg} [Harmonic series]
This is a good example of why the inverse of \Cref { thm:seriesnull} does not hold. Consider
\[
x_ n = \frac { 1} { n}
\]
This is a null sequence, but $ \series { k } \frac { 1 } { k } $ does not converge. (Why?)
\end { eg}
\begin { lem}
Let $ \rcseqdef { x } $ . Then
\[
\series { k} x_ n \text { converges} \iff \sum _ { k=N} ^ { \infty } x_ n \text { converges for some } N \in \natn
\]
\end { lem}
\begin { proof}
\reader
\end { proof}
\begin { thm} [Alternating series test]\label { thm:alttest}
Let $ \seq { x } \subset [ 0 , \infty ) $ be a monotonic decreasing null sequence. Then
\[
\series { k} (-1)^ k x_ k
\]
converges, and
\[
\left | \series { k} (-1)^ k x_ k - \series [N] { k} (-1)^ k x_ k \right | \le x_ { N+1}
\]
\end { thm}
\begin { proof}
Let $ s _ n = \series [ n ] { k } ( - 1 ) ^ k x _ n $ , and define the sub sequences $ a _ n = s _ { 2 n } $ , $ b _ n = s _ { 2 n + 1 } $ . Then
\begin { equation}
a_ { n+1} = s_ { 2n} - \underbrace { (x_ { 2n+1} - x_ { 2n+2} )} _ { \ge 0} \le s_ { 2n} = a_ n
\end { equation}
Hence, $ \seq { a } $ is monotonic decreasing. By the same argument, $ \seq { b } $ is monotonic decreasing. Let $ m, n \in \natn $ such that $ m \le n $ . Then
\begin { equation} \label { eq:act}
b_ m \le b_ n = a_ n - x_ { 2n+1} \le a_ n \le a_ m
\end { equation}
Therefore $ \seq { a } $ , $ \seq { b } $ are bounded. By \Cref { thm:monotone} , these sequence converge
\begin { align}
\seq { a} & \convinf a & \seq { b} & \convinf b
\end { align}
Furthermore
\begin { equation}
b_ n - a_ n = -x_ { 2n+1} \convinf 0 \implies a = b
\end { equation}
From \cref { eq:act} we know that
\begin { equation}
b_ m \le b = a \le a_ m
\end { equation}
So therefore
\begin { align}
|s_ { 2n} - a| & = a_ n - a \le a_ n - b_ n = x_ { 2n+1} \\
|s_ { 2n+1} - a| & = b - b_ n \le a_ { m+1} - b_ n = x_ { 2n+2}
\end { align}
\end { proof}
\begin { eg} [Alternating harmonic series]
\[
\begin { split}
s = \series { k} (-1)^ { k+1} \rec { k} & = 1 - \rec { 2} + \rec { 3} - \rec { 4} + \rec { 5} - \cdots \\
& = \left (1 - \rec { 2} \right ) - \rec { 4} + \left (\rec { 3} - \rec { 6} \right ) - \rec { 8} + \left (\rec { 5} - \rec { 10} \right ) - \rec { 12} + \cdots \\
& = \rec { 2} - \rec { 4} + \rec { 6} - \rec { 8} + \rec { 10} - \rec { 12} + \cdots \\
& = \rec { 2} \left (1 - \rec { 2} + \rec { 3} - \rec { 4} + \rec { 5} - \rec { 6} + \cdots \right ) \\
& = \rec { 2} s
\end { split}
\]
But $ s \in \left [ \rec { 2 } , 1 \right ] $ , this is an example on why rearranging infinite sums can lead to weird results.
\end { eg}
\begin { rem} \leavevmode
\begin { enumerate} [(i)]
\item The convergence behaviour does not change if we rearrange finitely many terms.
\item Associativity holds without restrictions
\[
\series { k} x_ k = \series { k} (x_ { 2k} + x_ { 2k-1} )
\]
\item Let $ I $ be a set, and define
\begin { align*}
I & \longrightarrow \realn \\
i & \longmapsto a_ i
\end { align*}
Consider the sum
\[
\sum _ { i \in I} a_ i
\]
If $ I $ is finite, there are no problems. However if $ I $ is infinite then the solution of that sum can depend on the order of summation!
\end { enumerate}
\end { rem}
\begin { defi}
Let $ \rcseqdef { x } $ . The series $ \series { k } x _ k $ is said to converge absolutely if $ \series { k } |x _ k| $ converges.
\end { defi}
\begin { rem}
Let $ \seq { x } \subset [ 0 , \infty ) $ . Then the sequence
\[
s_ n = \series [n] { k} x_ k
\]
is monotonic increasing. If $ \seq { s } $ is bounded it converges, if it is unbounded it diverges properly. The notation for absolute convergence is
\[
\series { k} |x_ k| < \infty
\]
\end { rem}
\begin { lem} \label { lem:absolutebounded}
Let $ \series { k } x _ k $ be a series. Then the following are all equivalent
\begin { enumerate} [(i)]
\item
\[
\series { k} x_ k \text { converges absolutely}
\]
\item
\[
\set [I \subset \natn \text{ finite}] { \sum _ { k \in I} |x_ k|} \text { is bounded}
\]
\item
\[
\forall \epsilon > 0 ~\exists I \subset \natn \text { finite} ~\forall J \subset \natn \text { finite} : ~~\sum _ { k \in J \setminus I} |x_ k| < \epsilon
\]
\end { enumerate}
\end { lem}
\begin { proof}
To prove the equivalence of all of these statements, we will show that (i) $ \implies $ (ii) $ \implies $ (iii) $ \implies $ (i). This is sufficient. First we prove (i) $ \implies $ (ii). Let
\begin { equation}
\series { n} |x_ n| = k \in [0, \infty )
\end { equation}
Let $ I \subset \natn $ be a finite set, and let $ N = \max I $ . Then
\begin { equation}
\sum _ { n \in I} |x_ n| \le \series [N] { n} |x_ n| \leexpl { Monotony of the partial sums} \series { n} |x_ n|
\end { equation}
Now to prove (ii) $ \implies $ (iii), set
\begin { equation}
K := \set [I \subset \natn \finite] { \sum _ { k \in I} |x_ k|}
\end { equation}
Let $ \epsilon > 0 $ . Then by definition of $ \sup $
\begin { equation}
\exists I \subset \natn \finite : ~~\sum _ { k \in I} |x_ k| > k - \epsilon
\end { equation}
Let $ J \subset \natn \finite $ . Then
\begin { equation}
k - \epsilon < \sum _ { k \in I} |x_ k| \le \sum _ { k \in I \cup J} |x_ k| \le K
\end { equation}
Hence
\begin { equation}
\sum _ { k \in J \setminus I} |x_ k| = \sum _ { k \in I \cup J} |x_ k| - \sum _ { k \in I} |x_ k| \le \epsilon
\end { equation}
Finally we show that (iii) $ \implies $ (i). Choose $ I \subset \natn \finite $ such that
\begin { equation}
\forall J \subset \natn \finite : ~~\sum _ { k \in J \setminus I} |x_ k| < 1
\end { equation}
Then $ \forall J \subset \natn \finite $
\begin { equation}
\sum _ { k \in J} |x_ k| \le \sum _ { k \in J \setminus I} |x_ k| + \sum _ { k \in I} |x_ k| \le \sum _ { k \in I} |x_ k| + 1
\end { equation}
Therefore $ \series [ n ] { k } |x _ k| $ is bounded and monotonic increasing, and hence it is converging. So $ \series { k } |x _ k| < \infty $ .
\end { proof}
2021-03-26 21:56:06 +00:00
\begin { thm} \label { 259}
2021-03-22 23:25:22 +00:00
Every absolutely convergent series converges and the limit does not depend on the order of summation.
\end { thm}
\begin { proof}
Let $ \series { k } x _ k $ be absolutely convergent and let $ \epsilon > 0 $ . Choose $ I \subset \natn \finite $ such that
\begin { equation}
\forall J \subset \natn : ~~\sum _ { k \in I} |x_ k| < \epsilon
\end { equation}
Choose $ N = \max I $ . Define the series
\begin { equation}
s_ n = \series [n] { k} x_ k
\end { equation}
Then for $ n \le m \le N $
\begin { equation}
|s_ n - s_ m| \le \sum _ { k=m+1} ^ n |x_ k| \le \sum _ { k \in \set { 1, \cdots , n} \setminus I} |x_ k| < \epsilon
\end { equation}
Hence $ s _ n $ is a Cauchy sequence, so it converges. Let $ \phi : \natn \rightarrow \natn $ be a bijective mapping. According to \Cref { lem:absolutebounded} the series $ \series { k } x _ { \phi ( n ) } $ converges absolutely. Let $ \epsilon > 0 $ . According to the same Lemma
\begin { equation}
\exists I \subset \natn \finite ~\forall J \subset \natn \finite : ~~\sum _ { k \in J \setminus I} |x_ k| < \frac { \epsilon } { 2}
\end { equation}
Choose $ N \in \natn $ such that
\begin { equation}
I \subset \set { 1, \cdots , N} \cap \set { \phi (1), \phi (2), \cdots , \phi (n)}
\end { equation}
Then for $ n \ge N $
\begin { equation}
\begin { split}
\left |\series { k} x_ k - \series [n] { k} x_ { \phi (k)} \right | & = \left | \sum _ { k \in \set { 1, \cdots , N} \setminus I} x_ k - \sum _ { k \in \set { \phi (1), \cdots , \phi (n)} \setminus I} x_ k \right | \\
& \le \sum _ { k \in \set { 1, \cdots , N} \setminus I} |x_ k| + \sum _ { k \in \set { \phi (1), \cdots , \phi (n)} \setminus I} |x_ k| < \epsilon
\end { split}
\end { equation}
Therefore
\begin { equation}
\limn \left ( \series [n] { k} x_ k - \series [n] { k} x_ { \phi (k)} \right ) = 0
\end { equation}
\end { proof}
\begin { thm}
Let $ \series { k } x _ k $ be a converging series. Then
\[
\left | \series { k} x_ k \right | \le \series { k} |x_ k|
\]
\end { thm}
\begin { proof}
\reader
\end { proof}
\begin { thm} [Direct comparison test]
Let $ \series { k } x _ k $ be a series. If a converging series $ \series { k } y _ k $ exists with $ |x _ k| \le y _ k $ for all sufficiently large $ k $ , then $ \series { k } x _ k $ converges absolutely. If a series $ \series { k } z _ k $ diverges with $ 0 \le z _ k \le x _ k $ for all sufficiently large $ k $ , then $ \series { k } x _ k $ diverges.
\end { thm}
\begin { proof}
\begin { equation}
\series [n] { k} |x_ k| \le \series [n] { k} y_ k \implies \series [n] { k} x_ k \text { bounded} \implbl { \cref { lem:absolutebounded} } \series { k} |x_ k| < \infty
\end { equation}
\begin { equation}
\series [n] { k} z_ k \le \series [n] { k} x_ k \implies \series { k} x_ k \text { unbounded}
\end { equation}
\end { proof}
\begin { cor} [Ratio test]
Let $ \seq { x } $ be a sequence. If $ \exists q \in ( 0 , 1 ) $ such that
\[
\left | \frac { x_ { n+1} } { x_ n} \right | \le q
\]
for a.e. $ n \in \natn $ , then $ \series { k } x _ k $ converges absolutely. If
\[
\left | \frac { x_ { n+1} } { x_ n} \right | \ge 1
\]
then the series diverges.
\end { cor}
\begin { proof}
Let $ q \in ( 0 , 1 ) $ and choose $ N \in \natn $ such that
\begin { equation}
\forall n \ge N: ~~\left |\frac { x_ { n+1} } { x_ n} \right | \le q
\end { equation}
Then
\begin { equation}
|x_ { N+1} | \le q|x_ N|, ~|x_ { N+2} | \le q|x_ { N+1} | \le q^ 2|x_ N|, ~\cdots
\end { equation}
This means that
\begin { equation}
\series { k} |x_ k| \le \series [N] { k} |x_ k| + \sum _ { k=N+1} ^ \infty q^ { k-N} \cdot |x_ N| < \infty
\end { equation}
Hence, $ \series { k } x _ k $ converges absolutely. Now choose $ N \in \natn $ such that
\begin { equation}
\forall n \ge N: ~~\left |\frac { x_ { n+1} } { x_ n} \right | > 1
\end { equation}
However this means that
\begin { equation}
|x_ { n+1} | \ge |x_ { n} | ~~\forall n \ge N
\end { equation}
So $ \seq { x } $ is monotonic increasing and therefore not a null sequence. Hence $ \series { k } x _ k $ diverges.
\end { proof}
\begin { cor} [Root test]
Let $ \seq { x } $ be a sequence. If $ \exists q \in ( 0 , 1 ) $ such that
\[
\sqrt [n] { |x_ n|} \le q
\]
for a.e. $ n \in \natn $ , then $ \series { k } x _ k $ converges absolutely. If
\[
\sqrt [n] { |x_ n|} \ge 1
\]
for all $ n \in \natn $ then $ \series { k } x _ k $ diverges.
\end { cor}
\begin { proof}
\reader
\end { proof}
\begin { rem}
The previous tests can be summed up by the formulas
\begin { align*}
\limn \left |\frac { x_ { n+1} } { x_ n} \right | & < 1 & \limn \sqrt [n] { |x_ n|} & < 1 \\
\limn \left |\frac { x_ { n+1} } { x_ n} \right | & > 1 & \limn \sqrt [n] { |x_ n|} & > 1
\end { align*}
for convergence and divergence respectively. If any of these limits is equal to $ 1 $ then the test is inconclusive.
\end { rem}
\begin { eg}
Let $ z \in \cmpln $ . Then
\[
\exp (z) := \sum _ { k=0} ^ \infty \frac { z^ k} { k!}
\]
converges. To prove this, apply the ratio test:
\[
\frac { |z|^ { k+1} k!} { (k+1)! |z|^ k} = \frac { |z|} { k+1} \conv { } 0
\]
The function $ \exp : \cmpln \rightarrow \cmpln $ is called the exponential function.
\end { eg}
\begin { rem} [Binomial coefficient]
The binomial coefficient is defined as
\begin { align*}
{ n\choose 0} & := 1 & { n\choose k+1} & = { n\choose k} \cdot \frac { n-k} { k+1}
\end { align*}
and represents the number of ways one can choose $ k $ objects from a set of $ n $ objects. Some rules are
\begin { enumerate} [(i)]
\item \[ { n \choose k } = 0 ~~ \text { if } k > n \]
\item \[ k \le n: ~~ { n \choose k } = \frac { n ! } { k ! ( n - k ) ! } \]
\item \[ { n \choose k } + { n \choose k - 1 } = { n + 1 \choose k } \]
\item \[ \forall x, y \in \cmpln : ~~ ( x + y ) ^ n = \series [ n ] { k } { n \choose k } x ^ ky ^ { n - k } \]
\end { enumerate}
\end { rem}
\begin { thm}
\[
\forall u, v \in \cmpln : ~~\exp (u+v) = \exp (u)\cdot \exp (v)
\]
\end { thm}
\begin { proof}
\begin { equation}
\begin { split}
\exp (u)\cdot \exp (v) = \left (\sum _ { n=0} ^ { \infty } \frac { u^ n} { n!} \right ) \cdot \left (\sum _ { m=0} ^ { \infty } \frac { v^ m} { m!} \right ) & = \sum _ { n=0} ^ { \infty } \sum _ { m=0} ^ { \infty } \frac { u^ nv^ m} { n!m!} \\
& = \sum _ { l=0} ^ { \infty } \sum _ { k=0} ^ { l} \frac { u^ kv^ { l-k} } { k!(l-k)!} \\
& =\sum _ { l=0} ^ { \infty } \frac { (u+v)^ l} { l!} \\
& = \exp (u+v)
\end { split}
\end { equation}
\end { proof}
\begin { rem}
We define Euler's number as
\[
e := \exp (1)
\]
We will also take note of the following rules $ \forall x \in \cmpln , n \in \natn $
\[
\exp (0) = \exp (x)\exp (-x) = 1 \implies \exp (-x) = \frac { 1} { \exp (x)}
\]
\[
\exp (nx) = \exp (x + x + x + \cdots + x) = \exp (x)^ n
\]
\[
\exp (x)^ { \frac { 1} { n} } = \exp (\frac { x} { n} )
\]
Alternatively we can write
\[
\exp (z) = e^ z
\]
\end { rem}
\begin { thm}
Let $ x, y \in \realn $ .
\begin { enumerate} [(i)]
\item
\[
x < y \implies \exp (x) < \exp (y)
\]
\item
\[
\exp (x) > 0 ~~\forall x \in \realn
\]
\item
\[
\exp (x) \ge 1 + x ~~\forall x \in \realn
\]
\item
\[
\limn \frac { n^ d} { \exp (n)} = 0 ~~\forall d \in \natn
\]
\end { enumerate}
\end { thm}
\begin { proof} \leavevmode
\begin { enumerate} [(i)]
\item \reader
\item For $ x \ge 0 $ this is trivial. For $ x < 0 $
\begin { equation}
\exp (x) = \frac { 1} { \exp (-x)} > 0
\end { equation}
\item For $ x \ge 0 $ this is trivial. For $ x < 0 $
\begin { equation}
\sum _ { k=0} ^ { \infty } \frac { x^ k} { k!}
\end { equation}
is an alternating series, and therefore the statement follows from \Cref { thm:alttest} .
\item Let $ d \in \natn $ . Then $ \forall n \in \natn $
\begin { equation}
0 < \frac { n^ d} { \exp (n)} < \frac { n^ d} { \sum _ { k=0} ^ { d+1} \frac { n^ k} { k!} } \convinf 0
\end { equation}
\end { enumerate}
\end { proof}
\begin { defi}
Define
\[
\sin , \cos : \realn \longrightarrow \realn
\]
as
\begin { align*}
\sin (x) & := \Im (\exp (ix)) \\
\cos (x) & := \Re (\exp (ix))
\end { align*}
\end { defi}
\begin { rem} \leavevmode
\begin { enumerate} [(i)]
\item Euler's formula
\[
\exp (ix) = \cos (x) + i\sin (x)
\]
\item $ \forall z \in \cmpln : ~~ \overline { \exp ( z ) } = \exp ( \bar { z } ) $
\[
|\exp (ix)|^ 2 = \exp (ix) \cdot \overline { \exp (ix)} = \exp (ix) \cdot \exp (-ix) = 1
\]
Also:
\[
1 = \cos ^ 2(x) + \sin ^ 2(x)
\]
On the symmetry of $ \cos $ and $ \sin $ :
\[
\cos (-x) + i\sin (-x) = \exp (-ix) = \overline { \exp (ix)} = \cos (x) - i\sin (x)
\]
\item From
\[
\exp (ix) = \sum _ { k=0} ^ { \infty } \frac { (ix)^ k} { k!} ~~~(i^ 0 = 1, i^ 1 = i, i^ 2 = -1, i^ 3 = -i, i^ 4 = 1, \cdots )
\]
follow the following series
\begin { align*}
\sin (x) & = \sum _ { k=0} ^ { \infty } \frac { (-1)^ k x^ { 2k+1} } { (2k+1)!} & \cos (x) & = \sum _ { k=0} ^ { \infty } \frac { (-1)^ k x^ { 2k} } { (2k)!}
\end { align*}
\item For $ x \in \realn $
\[
\begin { split}
\exp (i2x) & = \cos (2x) + i\sin (2x) \\
& = (\cos (x) + i\sin (x))^ 2 \\
& = \cos ^ 2(x) - \sin ^ 2(x) + 2i\sin (x)\cos (x)
\end { split}
\]
By comparing the real and imaginary parts we get the following identities
\begin { align*}
\cos (2x) & = \cos ^ 2(x) - \sin ^ 2(x) \\
\sin (2x) & = 2\sin (x)\cos (x)
\end { align*}
\item Later we will show that $ \cos $ as exactly one root in the interval $ [ 0 , 2 ] $ . We define $ \pi $ as the number in the interval $ [ 0 , 4 ] $ such that $ \cos ( \frac { \pi } { 2 } ) = 0 $ .
\[
\implies \sin (\frac { \pi } { 2} ) = \pm 1
\]
$ \cos $ and $ \sin $ are $ 2 \pi $ -periodic.
\end { enumerate}
\end { rem}
\begin { thm}
$ \forall z \in \cmpln $
\[
\limn \left (1 + \frac { z} { n} \right )^ n = \limn \left (1 - \frac { z} { n} \right )^ { -n} = \exp (z)
\]
\end { thm}
\begin { proof}
Without proof.
\end { proof}
\end { document}